Gamma Radiation Induced Effects in TeO2 Thin Films - Manisha Mohil; G. Anil Kumar (Журнал нано- та електронної фізики)
Gamma radiation induced effects on electrical and optical properties of thin films of tellurium dioxide (TeO2), a wide band gap semiconductor material, of different thicknesses prepared by thermal evaporation method have been studied in detail. The current-voltage characteristics for the thin films before and after gamma irradiation were analysed to obtain normalised current versus gamma dose plots at different applied voltages. The plots obtained clearly show that the normalised current increases almost linearly with the radiation dose up to certain limit and this limit is found to be dependent on thickness of the thin film. Beyond this limit the current is found to decrease. For gamma sources emitting higher gamma energy, this linear behaviour extends to higher radiation doses. The optical characterization of the as-deposited thin films as well as gamma irradiated thin films clearly shows that the optical band gap decreases with increase in the gamma radiation dose up to a certain limit. However, the optical band gap has been found to increase beyond this limit. The observed changes in electrical and optical properties clearly indicate the possibility of using TeO2 thin film as a gamma radiation dosimeter.